The Financing of the London Olympics 2012 and its economic effects on the U.K. - Khandelwal, Mohak (2010)
The Olympics are being seen as an event that can turn an ordinary city into a world city. The past has shown that hosting the games can make a country have enormous profits or, on the other hand, go into deep losses, and the enormous amounts of money invested in them are evidence of this. This paper aims to examine The United Kingdom’s preparations for the 2012 Olympic Games by focussing on the various costs that are incurred, in particular on the plans for a positive economic legacy, and finding out exactly how the London Olympics 2012 are being financed.